Universal noir #1 - Butler, Gerard (Universal Studios, 2022)
"Eine liebende Krankenschwester hilft einem durch den Krieg zum Verbrecher gewordenen Seemann. Düsteres psychologisches Melodram mit Akzenten des "schwarzen" Kriminalfilms ..." [filmdienst.de]
Original: USA 1948
Limited edition Blu-ray box set special features: 2019 restoration from a 2K scan ; original mono audio ; audio commentary with film historian Josh Nelson (2022) ; The John Player lecture with Joan Fontaine (1978, 63 mins): archival audio recording of the much-loved star in conversation with film critic Martin Shawcross at London’s National Film Theatre ; United action means victory (1939, 37 mins): documentary about the 1938–39 General Motors strike, with narration written by Kiss the blood off my hands screenwriter Ben Maddow ; original theatrical trailer ; image gallery: promotional and publicity material ; new and improved English subtitles for the deaf and hard of hearing ; UK premiere on Blu-ray
Bildformat 1.37:1
Keywords: Blu-Ray-Disc